Opportunities for Uneven-Aged Management in Second Growth Longleaf Pine Stands in Florida - Jennifer Lynn Gagnon; Eric J Jokela; Ajay Sharma; Jason G. Vogel (EDIS)
A discussion of traditional and alternative longleaf pine management practices, as well as a description of the process of converting an even-aged stand of mature longleaf pine to an uneven-aged stand.